2019
DOI: 10.1111/cogs.12766
|View full text |Cite
|
Sign up to set email alerts
|

Staying Together: A Bidirectional Delay–Coupled Approach to Joint Action

Abstract: To understand how individuals adapt to and anticipate each other in joint tasks, we employ a bidirectional delay–coupled dynamical system that allows for mutual adaptation and anticipation. In delay–coupled systems, anticipation is achieved when one system compares its own time‐delayed behavior, which implicitly includes past information about the other system’s behavior, with the other system’s instantaneous behavior. Applied to joint music performance, the model allows each system to adapt its behavior to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 51 publications
(95 reference statements)
1
49
0
Order By: Relevance
“…Previously used to detect functional connectivity or coupling within individuals’ brain networks ( Bruns et al, 2000 ; Doron et al, 2012 ; Hipp et al, 2012 ), we applied AECs to detect coupling between individuals. Although the current findings are agnostic with respect to the relationship between phase-resetting mechanisms of endogenous neural oscillations and transient ERPs in response to rhythmic auditory stimuli ( Haegens and Golumbic, 2018 ; Novembre and Iannetti, 2018 ), the measures of enhanced power and amplitude envelopes presented here offer insights into the bidirectional (Leader-Follower) period coupling typical of skilled musical ensembles ( Demos et al, 2019 ).…”
Section: Discussionmentioning
confidence: 72%
“…Previously used to detect functional connectivity or coupling within individuals’ brain networks ( Bruns et al, 2000 ; Doron et al, 2012 ; Hipp et al, 2012 ), we applied AECs to detect coupling between individuals. Although the current findings are agnostic with respect to the relationship between phase-resetting mechanisms of endogenous neural oscillations and transient ERPs in response to rhythmic auditory stimuli ( Haegens and Golumbic, 2018 ; Novembre and Iannetti, 2018 ), the measures of enhanced power and amplitude envelopes presented here offer insights into the bidirectional (Leader-Follower) period coupling typical of skilled musical ensembles ( Demos et al, 2019 ).…”
Section: Discussionmentioning
confidence: 72%
“…Interestingly, we also observed that task-related asymmetries, such as dissimilarity between musical parts, may increase the coordinative stability between co-performers. Accordingly, individuals leading music education activities via NMP might aim to prioritize exercises involving complementary, asymmetric musical tasks, especially in cases where ATL is variable or cannot be kept to a minimum around 20 ms. Further experimental research into the effects of ATL on interpersonal coordination during musical performance, including the ongoing development of computational models capturing multi-agent coordination in the context of informational delays (e.g., Rottondi et al, 2016;Demos et al, 2019;Heggli et al, 2019;Román et al, 2019;Shahal et al, 2020), is invaluable to the continued improvement of NMP. Performers have also indicated that physical separation alone poses challenges to music ensemble performance independent of those introduced by ATLs, noting that the associated hindrances to tuning, blending, and taking musical risks can all inhibit creativity (Iorwerth and Knox, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, strong anticipatory behavior is fundamentally rooted in the direct (action-perception) coupling of an agent with its environment, forming a dynamical system that is driven towards stable relationships between its components (as for example described by the relative phase in periodic behaviors). In this regard, anticipatory behavior in joint motor coordination may be the outcome of a momentto-moment alignment of actions to perceptual information (Kelso, 1995;Wilson & Golonka, 2013) , of the introduction of small time-delayed self-feedback (Demos, Layeghi, Wanderley, & Palmer, 2019;Roman, Washburn, Large, Chafe, & Fujioka, 2019;Stepp & Turvey, 2010;Washburn, Kallen, Coey, Shockley, & Richardson, 2015) , or of long-term complexity matching of joint behavior (Fine, Likens, Amazeen, & Amazeen, 2015;Marmelat & Delignières, 2012) . These studies provide valuable mathematical methods for the analysis and modeling of complexity and fluctuation structures in joint behavior, with a central focus on nonlinear, time-varying characteristics of this behavior.…”
Section: Discussionmentioning
confidence: 99%